Evaluate the limit x → 1 lim x − 1 x 2 0 1 5 − 1 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
L'Hopital's rule also makes the problem very easy! The numerator becomes 2 0 1 5 x 2 0 1 4 and the denominator 1 after differentiating numerator and denominator.
Log in to reply
I used to solve limits without L'hôpital's rule, is like my last tool for solving limits xd
Nice solution!
We can apply L'Hôpital's rule which states x → c lim g ( x ) f ( x ) = x → c lim g ′ ( x ) f ′ ( x )
x → 1 lim x − 1 x 2 0 1 5 − 1 = x → 1 lim 1 2 0 1 5 x 2 0 1 4 = 2 0 1 5
We simply use the property:
There is an elementary proof for this as well by taking
x
=
1
+
h
where
h
is infinitesimally small.Then the expression changes to
h
(
1
+
h
)
n
−
1
(we converted it from
x
to
h
).We can expand numerator using Binomial Expansion.After expanding we cancel out
h
from numerator and denominator.The final result is
But since
h
tends to
0
the limit reduces to
n
.
Q . E . D .
lim x→1 (x^2015-1)/(x-1) =lim x→1 d/dx(x^2015-1)/d/dx(x-1) =lim x→1 2015x/1=2015
We know, Lim (x^n-a^n)/(x-a)=n a^(n-1) [as x->a] So,the answer would be 2015 (1)^2014=2015
Problem Loading...
Note Loading...
Set Loading...
x → 1 lim x − 1 x 2 0 1 5 − 1 = x → 1 lim x − 1 ( x − 1 ) ( x 2 0 1 4 + x 2 0 1 3 + x 2 0 1 2 + . . . + x 2 + x + 1 ) = 2 0 1 5